تأثير الصوت من كلام البشر نموذجاً قوله تعالى: إِ ن أَنكَرَ األَْ أ صوَاتِ لَصَأو ت ا أ لَْمِير - Md. Nazmul Hasan,; Md. Mozammel Hoque, (Universiti Kebangsaan Malaysia, 2015)
This article aims to expose the role of sound from people’s speech and its effects when they address each other, from the light of the Holy Qur’an and Sunnah. Sound has great importance to convey the message of personal objectives among the people. We speak everyday with our parents, relatives, neighbours and others within our own community and beyond. Consequently, proper addressing with soft sound has paramount benefits. Nowadays many people do not care about this sensitive part, due to the sound intonation sometimes leads to awaken feelings, either positive or negative corner. The Qur’an and the Sunnah give special value in this aspect in the time of conversation with people regardless their religions and tribes even with unbelievers. Allah mentions in the holy Quran when he addressed to Moses and Aaron (peace be upon them): “But speak to him mildly; perchance he may take warning or fear (Allah)” (20:44). This verse indicates to the wonderful style of dialogue with people even if he denies God and does not believe in the Creator of this prolonged universe. Moreover in this paper we will discuss about the impact of sound when they speak with other as well as importance of way for conversation. Apart from that the solution for the negative effects of coarse sounds, in this research we will follow analytical and inductive approach.